A review of the genus Tzustigmus Finnamore (Hymenoptera: Crabronidae: Pemphredoninae) from India with the description of a new species - Rajan, Tessy; Kumar, P. Girish; Sureshan, P.m. (Zootaxa, 2021)
The genus Tzustigmus Finnamore (Crabronidae: Pemphredoninae) from India is reviewed and a modified key to the world species is provided. A new species T. sahyadriensis Tessy, Girish Kumar & Sureshan sp. nov., from Kerala is described and illustrated.